The role of Vibrio vulnificus virulence factors and regulators in its infection-induced sepsis - Li, Gang; Wang, Ming-Yi (Folia microbiologica, 2020)
Due to the development of Marine aquaculture, infections caused by Vibrio vulnificus are common all over the world. Symptoms of V. vulnificus infection vary from gastrointestinal illness to septicemia. After infection with V. vulnificus, some patients showed gastrointestinal symptoms, including vomiting, fever, diarrhea, and so on. Others appeared wound infection at the site of contact with bacteria, and even developed sepsis. Once it develops into sepsis, the prognosis of patients is very poor. However, its underlying pathogenic mechanism remains largely undetermined. Growing evidence shows that it can induce primary septicemia mainly via essential virulence factors and regulators. Therefore, it is important to identify the factors that play roles in sepsis. In this review, we systematically expounded the role of V. vulnificus virulence factors and regulators in its infection-induced sepsis in order to provide useful information for the treatment and prevention of V. vulnificus.
Keywords: faktory virulence; Bacterial Proteins; V. vulnificus; Metalloprotease; Virulence factors and regulators; infekce bakteriemi rodu Vibrio; sepse; Animals; Vibrio vulnificus; Humans; VvhA; Vibrio Infections; lidé; zvířata; Sepsis; Virulence Factors; bakteriální proteiny